PENGARUH POLA DISTRIBUSI HUJAN TERHADAP PENYIMPANGAN DEBIT PUNCAK HIDROGRAF SATUAN SINTETIK NAKAYASU - Tunas, I Gede; Tanga, Arody (MEKTEK, 2011)
There are many methods which used to analyze flood hydrograph, started from the simplest Rational Methods to the most complex mathematical models. One of them is Nakayasu Synthetic Unit Hydrograph (SUH) which has been known and used in wide area. Without realized, actually the use of the methods has been given a large deviation if compared with the measured river hydrograph. It is especially caused by the using of rainfall distribution pattern which be the input of the Nakayasu SUH Methods. This research was conducted to investigate the effect of rainfall distribution pattern to the peak discharge of Nakayasu SUH Methods using some rainfall distribution pattern such as Mononobe, ABM and Tadashi Tanimoto which applied on Bangga watershed. The result of the research using 10 elected flood data show that the average deviation from the biggest to the smallest, respectively are Mononobe (69.42 %), ABM (59.44 %) and Tadashi Tanimoto (22.42 %)